Model of earthen foundation with reinforcement in a deep excavation - Andrzej Surowiecki; Zenon Zamiar (Communications - Scientific letters of the University of Zilina, 2000)
In this paper, the results of model investigation of strength characteristics are discussed for the case of horizontally reinforced loose soil medium. The characteristics are then employed to create a model with vertical reinforcement. The vertical reinforcement has been proposed for the model of earthen foundation in a deep excavation whose bottom is subjected to displacement.